Photoinduced superhydrophilicity of TiO2 thin film with hierarchical Cu doping - Liu, Zhifeng (2013)
Hydrophilic Cu–TiO2 thin films with a gradient in the Cu concentration were prepared on glass by layer-by-layer dip-coating from TiO2 precursors. The effects of the Cu doping on the structure and properties of TiO2 self-cleaning thin films are discussed. The Cu gradient markedly affects the hydrophilicity of the films, with the water contact angle significantly reduced compared with those of the pure or uniformly doped TiO2 thin films. This enhanced hydrophilicity is explained by the more efficient absorption of the solar light and by the reduced recombination of photoexcited electrons and holes in the TiO2 films containing a gradient of Cu dopants.